Factors on Lecture Immersion among College Students in Online Learning Environments- A Physocological Behavioural Study - Jiwon Yoon, Namjoo Je, Meera Park (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: The objective of this research is to classify the degree of self-determination, major correctness, self-leadership, lecture immersion, and the connection among this factor. It also determines the factors affecting the lecture immersion for college students; Methods: The data were collected through online questionnaires answered by 173 university students in G province on December 2020. This is evaluated by IBM SPSS WIN/25.0. Questionnaire is comprised of 99 questions assessing overall features, self-determination, major suitability, and lecture immersion in a virtual education situation. Results: A general characteristics is measured by their occurrence, mean, and standard deviation while the dissimilarity of variables was evaluated by t-test and one-way ANOVA. The post analysis is evaluated using Scheffe's test. Pearson's relationship was used to examine the relationship among each variable. Factors influencing lecture immersion were obtained by stepwise regression. The factors most influencing the subject's lecture immersion were self-leadership (β= .539, p< .001), self-determination (β= .184, p= .019), and main suitability (β= -. 173, p= .036). The descriptive power of the framework is 33.4%. Conclusions: To improve the lecture immersion in the non-face-to-face era, it is necessary to give learners a choice, provide informational feedback, and create an autonomous learning environment.